2021
DOI: 10.31014/aior.1994.04.02.165
|View full text |Cite
|
Sign up to set email alerts
|

Health Insurance Uptake and Affordability of Care Among Patients with Hypertension in a Federal Teaching Hospital in Southwestern Nigeria

Abstract: This study aims to assess health insurance uptake and affordability of care among patients with hypertension in a Federal Teaching Hospital in Southwestern Nigeria. This was a cross sectional study involving 138 hypertensive patient selected through systematic random sampling technique from the cardiology clinic of a Federal Teaching Hospital. A semi-structured, interviewer administered questionnaire was used to collect data. Analysis was done using Statistical Package for Social Sciences (SPSS) version 21. A … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 6 publications
3
4
0
Order By: Relevance
“…One of the factors that have been found to affect enrollment into community and private health insurance schemes is poor awareness. 12,37,38 In this study the awareness rate of health insurance was low and is comparable to findings by Ipinnimo et al 29…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…One of the factors that have been found to affect enrollment into community and private health insurance schemes is poor awareness. 12,37,38 In this study the awareness rate of health insurance was low and is comparable to findings by Ipinnimo et al 29…”
Section: Discussionsupporting
confidence: 89%
“…36 One of the factors that have been found to affect enrollment into community and private health insurance schemes is poor awareness. 12,37,38 In this study the awareness rate of health insurance was low and is comparable to findings by Ipinnimo et al 29 The current study also showed that high level of paternal education; parental occupational status and the overall social status of the household are all factors that are associated with health care financing method of the household, such that more household with high paternal educational levels, civil servants and higher social status had health insurance. Similar findings were reported in other studies.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…[6] Also, the majority of the people pay for healthcare out-of-pocket with <5% of the population being captured under the National Health Insurance Scheme. [7] The inflation in healthcare is more of cost-push inflation (from increase in the cost of production) and to some extent build-in inflation (expectations that inflation will continue leading to wages increase). [1] The rise in the cost of health care services and other products has led to the decrease healthcare seeking behavior of the populace, especially those without health insurance cover, consequently, leading to delay elective care.…”
mentioning
confidence: 99%